2018
DOI: 10.1039/c7sc05104b
|View full text |Cite
|
Sign up to set email alerts
|

Highly sensitive and stable zwitterionic poly(sulfobetaine-3,4-ethylenedioxythiophene) (PSBEDOT) glucose biosensor

Abstract: A zwitterionic poly(sulfobetaine-3,4-ethylenedioxythiophene) (PSBEDOT)-based glucose biosensor was fabricated via encapsulating glucose oxidase (GOx) in a one-step electropolymerization method.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
44
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 61 publications
(47 citation statements)
references
References 44 publications
2
44
0
1
Order By: Relevance
“…[1][2][3][4] Extensive research demonstrated that zwitterionic polymers and polymers containing poly(ethylene glycol) components (referred to as "PEG materials" in this article) exhibit excellent antifouling activities. [5][6][7][8][9] It is believed that the strong surface hydration of such polymers mediates their excellent antifouling performance. [10][11][12][13] With strong surface hydration, it is difficult for biological media (e.g., protein molecules, bacteria, marine organisms, etc.)…”
Section: Introductionmentioning
confidence: 99%
“…[1][2][3][4] Extensive research demonstrated that zwitterionic polymers and polymers containing poly(ethylene glycol) components (referred to as "PEG materials" in this article) exhibit excellent antifouling activities. [5][6][7][8][9] It is believed that the strong surface hydration of such polymers mediates their excellent antifouling performance. [10][11][12][13] With strong surface hydration, it is difficult for biological media (e.g., protein molecules, bacteria, marine organisms, etc.)…”
Section: Introductionmentioning
confidence: 99%
“…are highly tunable in nature and can be altered by merely substituting the monomers with donor/acceptor moieties to obtain emission in the near infrared (NIR) region. These conjugated polymers find promising applications in solar cells, 11 biosensing 12,13 and bioimaging. 14–16 Several investigations have been reported on the design of donor–acceptor based conjugated polymers for their potential application in bio-imaging and photodynamic therapy.…”
Section: Introductionmentioning
confidence: 99%
“…By this antifouling polymer coating, the sensor presents a high linearity ( R 2 = 0.9874) from 0.1 to 0.5 mM. In contrast to antifouling properties of PEDOT–GOx coating, PSBEDOT–GOx showed better antifouling properties for blood plasma and fibrinogen proteins [ 176 ].…”
Section: Semi-implantable Device For In Vivo Applicationsmentioning
confidence: 99%